Uncertainty monitoring and information seeking in non-primate animals: Meta-analysis and systematic review - Qu, Zhizhen; Shi, Lei; So, Billy Chun Lung; Yin, Jia; Kwok, Sze Chai (Frontiers in Ethology, 2023)
Metacognitive abilities, the capacity to think about one's own thinking processes, offer a range of advantages that may drive their evolution in non-primate animals (NPAs). These advantages include enhancing adaptive decision-making in uncertain situations, efficient resource management, error detection and correction, and facilitating complex social interactions and problem-solving. In this comprehensive study, we have chosen two key paradigmsnamely, uncertainty monitoring and information-seeking tasksto study metacognitive phenomena in NPAs. The first paradigm involves an extensive metaanalysis of existing research, shedding light on how NPAs monitor and respond to uncertainty. We then transition to the second paradigm, which focuses on informationseeking behaviors, employing a different analytical approach. Our study aims to provide a holistic understanding of these cognitive processes in NPAs, contributing valuable insights into their cognitive complexity and ecological contexts. Through a coverage of 30 articles spanning 13 different NPA species, we bridge gaps in our understanding of metacognition beyond primates and explore potential divergent evolutionary paths, challenging assumptions about cognitive capability in NPAs.